REGIONAL TYPOLOGY APPROACH IN EDUCATION QUALITY IN WEST JAVA BASED ON AGRICULTURAL AND NON-AGRICULTURAL ECONOMIC STRUCTURE - Hendajany, Nenny; Rizal, Deden (Fakultas Pendidikan Ekonomi dan Bisnis, 2019)
West Java is the province in Indonesia with the highest population and has a location close to the capital. However, the condition of education in West Java is generally still low. This is estimated because there are imbalances between districts / cities. The research objective is to get a clear picture of the condition of education in West Java by using secondary data issued by the Central Statistics Agency. The research method uses descriptive analysis, with analysis tools of regional typology. The division of regional typologies from the two indicators produces four regional terms, namely developed regions, developed regions constrained, potential areas to develop, and disadvantaged areas. Based on the indicators of education quality and life expectancy in 2017, from 27 municipal districts in West Java there were 33.3% in developed regions, 18.52% in developed regions were constrained, 7.4% in potential developing regions, and 40.74 % in disadvantaged areas. Bandung and Bekasi regencies are included in developed regions. While the cities of Banjar and Tasikmalaya include potential developing regions. Regional division with three indicators, namely the average length of school, Location Quation, and life expectancy. This division produces three filled quadrants. Quadrant I has 29.6%, quadrant III has 18.5%, and the remaining 51.9% is in quadrant IV. The results of this regional typology show that there are imbalances in education and public health.